Response of broiler chickens to cassava peel and maize offal in cashewnut meal-based diets - K. Oyebimpe (Archivos de Zootecnia, 2006)
The effect of combinations of cassava peelmeal (CPM) and maize offal (MO) in cashewnutmeal (CNM) based diets was investigated usingunsexed day old Anak 2000 broilers. Controlmaize-based diet: without CPM, MO and CNM.Each of diets 2, 3 and 4 contained 300 g/kg CNMand (g/kg): 300 MO + 100 CPM; 200 MO + 200 CPMand 100 MO + 300 CPM, respectively. Feed intakeincreased (p<0.05) while weight gain decreasedcompared to the control. Diet 3 gave the best(p<0.05) feed to gain ratio. Protein intake washighest (p<0.05) on diets 2 and 4. Crude fibredigestibility decreased while the cost of producinga kg of broiler reduced in the MO + CPM diets(p<0.05). The 200 g/kg MO + 200 g/kg CPMcombination can replace maize in broiler dietswithout adverse effects.